The Role of Substrate Mediated Allostery in the Catalytic Competency of the Bacterial Oligosaccharyltransferase PglB - Morgan, Brittany R.; Massi, Francesca (Frontiers in Molecular Biosciences, 2021)
The oligosaccharyltransferase of Campylobacter lari (PglB) catalyzes the glycosylation of asparagine in the consensus sequence N-X-S/T, where X is any residue except proline. Molecular dynamics simulations of PglB bound to two different substrates were used to characterize the differences in the structure and dynamics of the substrate-enzyme complexes that can explain the higher catalytic efficiency observed for substrates containing threonine at the +2 position rather than serine. We observed that a threonine-containing substrate is more tightly bound than a serine-containing substrate. Because serine lacks a methyl group relative to threonine, the serine-containing peptide cannot stably form simultaneous van der Waals interactions with T316 and I572 as the threonine-containing substrate can. As a result, the peptide-PglB interaction is destabilized and the allosteric communication between the periplasmic domain and external loop EL5 is disrupted. These changes ultimately lead to the reorientation of the periplasmic domain relative to the transmembrane domain such that the two domains are further apart compared to PglB bound to the threonine-containing peptide. The crystal structure of PglB bound to the peptide and a lipid-linked oligosaccharide analog shows a pronounced closing of the periplasmic domain over the transmembrane domain in comparison to structures of PglB with peptide only, indicating that a closed conformation of the domains is needed for catalysis. The results of our studies suggest that lower enzymatic activity observed for serine versus threonine results from a combination of less stable binding and structural changes in PglB that influence the ability to form a catalytically competent state. This study illustrates a mechanism for substrate specificity via modulation of dynamic allosteric pathways.